Pharmacists and medication adherence in asthma: a systematic review and meta-analysis. Issue 2 (23rd August 2018) - Mes, Marissa Ayano; Katzer, Caroline Brigitte; Chan, Amy Hai Yan; Wileman, Vari; Taylor, Stephanie Jane Caroline; Horne, Rob
The Lancet Asthma Commission highlighted that non-adherence remains a persistent barrier within asthma care. Medical consultations remain pivotal in addressing non-adherence, but interest in additional adherence support from pharmacists is increasing. This systematic review and meta-analysis aims to evaluate how effective pharmacist-led interventions are in improving medication adherence in adults with asthma. Studies were included if they had adult participants with asthma, pharmacist-led or collaborative care interventions, randomised controlled trial designs comparing interventions with usual pharmacist care, and a medication adherence outcome. We analysed adherence data using the standardised mean difference ( d ) and the remaining data were synthesised narratively. From 1159 records, 11 were included in the narrative synthesis and nine in the meta-analysis. The meta-analysis for adherence produced a medium effect size of d =0.49 (se =0.08, 95% CI 0.35–0.64, p<0.0001) with low statistical heterogeneity. In line with the Perceptions and Practicalities Approach, interventions targeted to address both the perceptions and practicalities that influence individual motivation and ability to adhere were more effective. Contextual factors (country and healthcare setting) were also influential. Our findings suggest that with adequate remuneration and integration into asthma care, pharmacists can help improve adherence in asthma. Pharmacist-led interventions can improve medication adherence in people with asthma http://ow.ly/IefK30kA6Z5